PSMD3-ILF3 signaling cascade drives lung cancer cell proliferation and migration - Jin Zhang; Qianli Ma; Qiduo Yu; Fei Xiao; Zhenrong Zhang; Hongxiang Feng; Chaoyang Liang (Biology Direct, 2023)
Abstract Background Proteasome 26S subunit, non-ATPase 3 (PSMD3) has been reported to participate in various human cancers. Nevertheless, the function of PSMD3 in lung cancer (LC) remains unclear. Methods RT-qPCR and western blot were used to detect the expression of PSMD3 in LC tissues form TCGA database and clinical samples, and LC cell lines. To study the effect of PSMD3 on LC cell proliferation, migration, invasion, and apoptosis, siRNAs targeting PSMD3 were synthesized and overexpressed plasmids were constructed. CCK-8 assay, Transwell assay, and etc. were used to evaluate the results. Tumor xenograft model was used to evaluate the function of PSMD3 on tumor growth. CO-IP and MS were used to scan the proteins that bind with PSMD3. The interaction between PSMD3 and ILF3 in lung cancer cells were studied using IF staining, CHX protein stability, and ubiquitination assay. Additionally, the effect of ILF3 on cell progression and LC tumor growth was demonstrated by conducting a recovery assay using siILF3 and an ILF3 inhibitor YM155. Results We observed that PSMD3 was significantly overexpressed in LC tissues and cells, which indicated a poor prognosis. Meanwhile, we found that PSMD3 promoted cell proliferation, migration, and invasion of LC cells. We also determined that PSMD3 stabilized the protein expression of ILF3 and the deubiquitination of ILF3 in lung cancer cells. Furthermore, animal experiments showed that the ILF3 inhibitor YM155 could suppress tumor growth with the presence of PSMD3. Conclusions PSMD3 collectively regulated the stability of ILF3 protein and facilitated the ubiquitination of endogenous ILF3 in LC, which ultimately promoted the progression of LC cells. The PSMD3/ ILF3 axis could potentially be used as a novel strategy for both diagnosis and treatment of LC.